A success model for cyber threat intelligence management platforms. Issue 111 (December 2021) - Zibak, Adam; Sauerwein, Clemens; Simpson, Andrew
Abstract: The increasingly persistent and sophisticated threat actors, along with the sheer speed at which cyber attacks unfold, have made timely decision making imperative for ensuring the continued security of most organisations. Consequently, threat intelligence management platforms have been widely adopted to assist organisations in creating and participating in inter-organisational sharing efforts to protect against cyber attacks. Measuring the effectiveness and success of these platforms is critical to understanding how such products and services should be designed, implemented and used. Nevertheless, it is a fact that research and practice lack a common understanding of factors influencing the success of threat intelligence management platforms. To investigate these issues, we adopted the DeLone and McLean information system success model to threat intelligence sharing and employed a survey-based approach to collect data from 152 security professionals for its empirical assessment. Subsequently, we identified several factors that are decisive for the organisational success of a threat intelligence management platform.